2021
DOI: 10.1002/anie.202115394
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective O‐Glycosylations by Pyrylium Salt Organocatalysis**

Abstract: Despite many years of invention, the field of carbohydrate chemistry remains rather inaccessible to nonspecialists,w hichl imits the scientific impact and reacho ft he discoveries made in the field. Aiming to increase the availability of stereoselective glycosylation chemistry for nonspecialists,w eh ave discovered that several commercially available pyrylium salts catalyze stereoselective O-glycosylations of aw ide range of phenols and alkyl alcohols.T his catalytic reaction utilizes trichloroacetimidates,a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 70 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Interestingly, PhSiF 3 afforded a cleaner reaction and higher stereoselectivity for a diol substrate (e.g., 180 in Figure e) than a mono-ol one as a glycosyl acceptor, probably because generation of a hexacoordinated intermediate is possible with PhSiF 3 , but not with PhBF 2 . Pedersen and co-workers also reported a stereoselective glycosylation reaction by pyrilium salts based on the same concept of acid–base catalysis . In their reaction, simple pyrilium salts, such as H 3 Pyry ( 182 ) and Me 3 Pyry ( 183 ), promoted stereoselective glycosylation reactions between various glycosyl trichloroacetimidates and glycosyl acceptors including phenols, carbohydrate alcohols, and a serine, although stereoselectivity was generally lower than the previous examples (Figure f).…”
Section: Acid–base Catalysis For Stereoselective Glycosylationmentioning
confidence: 91%
See 2 more Smart Citations
“…Interestingly, PhSiF 3 afforded a cleaner reaction and higher stereoselectivity for a diol substrate (e.g., 180 in Figure e) than a mono-ol one as a glycosyl acceptor, probably because generation of a hexacoordinated intermediate is possible with PhSiF 3 , but not with PhBF 2 . Pedersen and co-workers also reported a stereoselective glycosylation reaction by pyrilium salts based on the same concept of acid–base catalysis . In their reaction, simple pyrilium salts, such as H 3 Pyry ( 182 ) and Me 3 Pyry ( 183 ), promoted stereoselective glycosylation reactions between various glycosyl trichloroacetimidates and glycosyl acceptors including phenols, carbohydrate alcohols, and a serine, although stereoselectivity was generally lower than the previous examples (Figure f).…”
Section: Acid–base Catalysis For Stereoselective Glycosylationmentioning
confidence: 91%
“…Pedersen and co-workers also reported a stereoselective glycosylation reaction by pyrilium salts based on the same concept of acid−base catalysis. 127 In their reaction, simple pyrilium salts, such as H 3 Pyry (182) and Me 3 Pyry (183), promoted stereoselective glycosylation reactions between various glycosyl trichloroacetimidates and glycosyl acceptors including phenols, carbohydrate alcohols, and a serine, although stereoselectivity was generally lower than the previous examples (Figure 25f). Notably, this catalyst accommodates sterically demanding substrates.…”
Section: Acid−base Organocatalystsmentioning
confidence: 97%
See 1 more Smart Citation
“…Very recently Nielsen et al (2022 ) reported the pyrrylium catalyst (H 3 Pypy) catalyzed β-selective glycosylation of trichloroacetimidate donors. Reaction of reactive carbohydrate or phenol acceptors with α-trichloroacetimidate donor ( 1 ) in the presence of 0.1 equivalent of H 3 Pypy catalyst generated their corresponding β-glycosides ( 3 ) in good yield and stereoselectivity (VII in Scheme 5 ).…”
Section: Techniques For 12- Trans Selective Glycos...mentioning
confidence: 99%
“…It is noteworthy that a Schreiner thiourea catalyst with a halogen bond donor such as 2-iodoimidazolium salt has been developed to afford 1,2-cis N-glycoside from glycosyl trichloroacetimidate and amide of protected Asn (Li G et al, 2018). Pyrilium salt as an alternative organocatalyst effectively promotes the glycosylation of α and β-glycosyl trichloroacetimidate via S N 2-type inversion to afford β-(1,2cis manno-) and α-(1,2-cis gluco-) glycosides, respectively (Figure 2B2) (Nielsen et al, 2022).…”
Section: Recent Advances On 12-cis Glycosylations By Intermolecular C...mentioning
confidence: 99%